(3MGdI GdVQhQI h GdeSFhdjI GdOhdjI aj GdbGfhf GdOhdj GdYGe (B/ s - (3ehSi LGHQ ehSi CMeO GdCScfOQGfis; (3YGFTI QGJHs; (3eMeO SGeM YeQh s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JYJHQ MGdI GdVQhQI CMO ehVhYGJ GdbGfhf GdOhdj GdJj CKjQ HTCfgG LOdB abgjB hGSYB(B: (3NGUI CfgG CUHMJ JcJSj CgejI NGUI aj GdbGfhf GdOhdj GdeYGUQ (B. (3MjK cGf GdgOa ef Jdc GdQSGdI JbOje OQGSI TGedI h JCUjdjI dMGdI GdVQhQI(B: (3hhVY eaghe bGfhfj LGeY eGfY dgG aj GdbGfhf GdOhdj GdYGe(B: (3cPdc JMOjO GdWHjYI GdbGfhfjI dMGdI GdVQhQI aj GdbGfhf GdOhdj GdYGe ef chfgG Vef CSHGH GdEHGMI Ch ehGfY GdeSFhdjI Ch MGdI GSJKfGFjI JbJUQ Ydi EUdGM GdVQQ abW s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi s
(3HHdjhLQGajG(B: (3UaMGJ (B312-339s
Keywords: (3GdVQhQI aj GdTQjYI GdESdGejIs; (3GdJONd GdGfSGfis; (3eMGceGJ fhQeHQL ddVQhQI GdMQHjI s; (3bVjI GdSajfI fHJhf s; (3aJhi JTjjO GdLOGQ GdaGUd HGdCQGVj GdadSWjfjI GdeMJdI s; (3GdeSFhdjI GdOhdjIs; (3MGdI GdVQhQI aj CMcGe GdeMceI GdeMceI GdOGFeI ddYOd GdOhdjs; (3GdWHjYI GdbGfhfjI dMGdI GdVQhQI s; (3MGdI GdVQhQIs; (3bVjI GdedLC Hjf chdheHjG hHjQh (B1950 s; (3QSGFd LGejIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs